DETERMINAN PERSEPSI DAN PERILAKU IBU DALAM MEMBACA LABEL MAKANAN RINGAN ANAK TK-SD BUMI SERPONG DAMAI - Salim, Ruth Brigitta; Pambudi, Wiyarni (Ebers Papyrus, 2021)
children can be truly guaranteed. If the reading of children’s snack labels is ignored by mothers, then it can have an impact in the form of children’s growth and development not being optimal. In Indonesia, based on the survey results of  National Consumer Protection Survey (BPKN) in 2007, only 6.7% of Indonesia’s population paid attention to the completeness of food labels. This study was conducted to determine perceptions, behaviors, and factors, which influence the perceptions and behaviors of mothers in reading the snack labels of kindergarten-elementary school children of School X in the area of Bumi Serpong Damai (BSD). This study used a cross-sectional method by conducting structured interviews through questionnaires. Mothers, who were included in the category of good perception, were mothers with a mode score 4, and those who were in the category of good behavior when the mode score was 5. After obtaining the data, the data was processed and analyzed by the T-Test. From 95 respondents, 62 respondents (65.3%) had poor perceptions in reading children's snack labels. A total of 73 respondents (76.8%) had poor reading behavior of children's snack labels. The factors studied consisted of internal and external factors. After statistical tests were accomplishedly and properly taken, the results showed significant differences for internal factors, namely the age and ethnicity of the respondents regarding the respondents' behaviors and reading abilities (p <0.05). While there were no significant differences in external factors. From the results of this study, it can be concluded that the perceptions and behavior of mothers, who have kindergarten-elementary school children in School X in BSD area are still not good.